Little Turkey in the Medan Maimun Area - Ginting, Nurlisa; Zahrah, Wahyuni; Nasution, Achmad Delianur; Sitorus, Muhammad Aria; Shafira Imanina; Ervina Lestari; Shayra Anastsasya Shafwani (Talenta Publisher, 2023)
Community service is one of the core activities of the Tri Dharma of Higher Education. This activity is carried out as an effort to apply practical scientific knowledge to comprehensively address community problems in the field by involving both the community and university lecturers collaboratively. The current community service activity focuses on urban spatial planning issues in the Jl. Mahkamah area, Medan Kota District, Medan City, North Sumatra. The theme of this project is